Sistem Informasi Reservasi Kamar Hotel Snukel Menggunakan Metode Analisis System Usability Scale - Melisa Hikari; Nana Suarna; Odi Nurdiawan (Ma'soem University, 2023)
Web-Based Snukel Hotel Reservation Information System, is an information system that focuses on reservation data entered by the receptionist relating to reservations in the hotel's business transactions. In the previous system, data was entered manually using MS.Excel. The risk that is owned is management that is less effective and efficient. The purpose of building this system is to help manage reservation data to be more effective and efficient, make it easier to enter reservation data and help manage data. So that transactions are recorded and stored properly. The system design is made using the system development life cycle (SDLC) approach with the Waterfall design method, the stages include system requirements analysis, system design, system implementation, system testing and system maintenance. Hotel guest reservation system, using PHP programming language MySql. The results of this study are systems that have been tested with a black box, the results of the black box test state that the system is running well and as expected. System analysis uses the SUS method so that it gets a score or accuracy of 77.33 which means that the system is feasible and well received by the user.